GLT-1 promoter activity in astrocytes and neurons of mouse hippocampus and somatic sensory cortex - De Vivo, Luisa; Melone, Marcello; Rothstein, Jeffrey D.; Conti, Fiorenzo (Frontiers in Neuroanatomy, 2010)
GLT-1 eGFP BAC reporter transgenic adult mice were used to detect GLT-1 gene expression in individual cells of CA1, CA3 and SI, and eGFP fluorescence was measured to analyze quantitatively GLT-1 promoter activity in different cells of neocortex and hippocampus. Virtually all GFAP+ astrocytes were eGFP+; we also found that about 80% of neurons in CA3 pyramidal layer, 10-70% of neurons in I-VI layers of SI and rare neurons in all strata of CA1 and in strata oriens and radiatum of CA3 were eGFP+. Analysis of eGFP intensity showed that astrocytes had a higher GLT-1 promoter activity in SI than in CA1 and CA3, and that neurons had the highest levels of GLT-1 promoter activity in CA3 stratum pyramidale and in layer VI of SI. Finally, we observed that the intensity of GLT-1 promoter activity in neurons is 1-20% of that measured in astrocytes. These results showed that in the hippocampus and neocortex GLT-1 promoter activity is observed in astrocytes and neurons, detailed the distribution of GLT-1 expressing neurons, and indicated that GLT-1 promoter activity in both astrocytes and neurons varies in different brain regions.